Shopee's Use of Dynamic Pricing in the Global Market - Ramadhan, Sonia; Yunis, Arma; Panorama, Maya (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
Dynamic pricing is an important strategy in the highly competitive e-commerce industry, including on global platforms like Shopee. This strategy enables real-time adjustment of product prices based on changes in market demand, competition, operational costs, and customer preferences. This research aims to explore the implementation of dynamic pricing strategy on Shopee in the context of global e-commerce. The theoretical framework used includes the concepts of pricing and consumer behavior as a basis for analysis. The results show that Shopee utilizes dynamic pricing to enhance competitiveness through strategic promotions such as flash sales, thereby expanding market share and increasing cross-border transaction volume. However, the implementation of this strategy also poses ethical challenges as well as significantly affects consumer behavior. Therefore, the management of dynamic pricing should be done judiciously by considering transparency and customer trust in order to maintain loyalty while optimizing company profits.